Attacking poverty with microcredit - Ahmed, Salehuddin, 1949-; Hakim, Muhammed Abdul (Palli Karma-Sahayak Foundation : The University Press Limited, 2004)
Papers presented at the conference held at PKSF Bhaban, Dhaka; with reference most to Bangladesh.